2014
DOI: 10.1118/1.4865784
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation imaging is a powerful tool to image brain microvasculature

Abstract: Synchrotron radiation (SR) imaging is a powerful experimental tool for micrometer-scale imaging of microcirculation in vivo. This review discusses recent methodological advances and findings from morphological investigations of cerebral vascular networks during several neurovascular pathologies. In particular, it describes recent developments in SR microangiography for real-time assessment of the brain microvasculature under various pathological conditions in small animal models. It also covers studies that em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
(67 reference statements)
0
17
0
1
Order By: Relevance
“…35 The spatial resolution of SRA can reach submicrons, approximately 1000 times higher than that of conventional X-ray absorption imaging, and it can be used for high-resolution imaging of the whole middle cerebral artery territory blood supply in living rodents. 53,54 Vessel density is an indicator of microvascular perfusion. Our results showed that NBP treatment increased the perfused vessel density.…”
Section: Discussionmentioning
confidence: 99%
“…35 The spatial resolution of SRA can reach submicrons, approximately 1000 times higher than that of conventional X-ray absorption imaging, and it can be used for high-resolution imaging of the whole middle cerebral artery territory blood supply in living rodents. 53,54 Vessel density is an indicator of microvascular perfusion. Our results showed that NBP treatment increased the perfused vessel density.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that a synchrotron radiation (SR) X-ray source can provide superior high spectral resolution and small divergence, and involves the delivery of lower doses of radiation. 6 Consequently, this monochromatized X-ray source has the potential to provide a novel imaging perspective for biological and medical applications. [4][5][6][7][8] Owing to the weak absorption rate of soft tissues, conventional X-ray absorption imaging cannot discriminate blood vessels from surrounding structures without the use of contrast agents.…”
mentioning
confidence: 99%
“…6 Consequently, this monochromatized X-ray source has the potential to provide a novel imaging perspective for biological and medical applications. [4][5][6][7][8] Owing to the weak absorption rate of soft tissues, conventional X-ray absorption imaging cannot discriminate blood vessels from surrounding structures without the use of contrast agents. 9,10 However, phase contrast imaging (PCI), which utilizes SR technology and X-ray phase shift, is approximately 1000 times more sensitive than conventional X-ray absorption contrast imaging.…”
mentioning
confidence: 99%
“…Functional imaging of small animal models has been accomplished by introduction of various modalities, including micro-PET [16] and micro-SPECT [17], while anatomic imaging of soft tissue has been realized by means of magnetic resonance microscopy [18,19], micro-ultrasound [20,21] and micro-CT [22] with dual X-ray energy [23], with nanoparticles [24,25], and with contrast media [26]. Synchrotron radiation has also been also used but it has been suffering from very high facility cost and limited user base [27]. Recently, multimodality micro-imaging, such as micro-PET/CT, micro-MR/PET, and micro-SPECT/CT, have been used to realize fusion of functional and anatomic information [28][29][30][31].…”
Section: Present Status Of X-ray Based Medical and Biomedical Imagingmentioning
confidence: 99%